Reproduction parameters in Phrynobatrachus latifrons Ahl 1924, a frog in degraded areas of Banco National Park (Ivory Coast) | JBES 2021 - Blayda, Tohe; Namingonan, Alla; Emmanuel, Assemian, N’guessan (My University, 2022)
The study of the reproductive ecology of Phrynobatrachus latifrons at the fish farm of the Banco National Park showed that the smallest mature individual measures 12.5mm in males and 17mm in females. All individuals greater than 18.9mm in males and 24.26mm in females are mature. The size of first sexual maturity (L50) calculated is 15.37mm for males against 20.20mm for females. The sex ratio, with the exception of the small rainy season is in favor of the females. Absolute fertilitymuzzle-anus length and absolute fecundity/body weight ratios showed a low correlation. The breeding activities of P. latifrons occur in the dry season as well as in the rainy season.
Keywords: Banco national park; Biodiversity; Environmental Sciences; First breeding size; Fish farm; Ivory Coast; Phrynobatrachus latifrons; Reproduction